Absent Pulmonary Valve Syndrome with Left Hemitruncus - Aly, Ashraf M.; Reid, Deborah A.; Jiwani, Amyn K.; Desai, Pooja H. (American Journal of Perinatology Reports, 2012)
Absent pulmonary valve syndrome (APVS) is a rare congenital heart defect, usually associated with tetralogy of Fallot (TOF), although other associations have been described. A pregnant woman was referred to fetal echocardiography clinic from the Maternal Fetal Medicine department due to abnormal findings on routine antenatal ultrasound, showing a pulsatile cystic mass above the left atrium and a suspected TOF. A fetal echocardiogram confirmed the presence of TOF/APVS. The pulsatile cystic mass was the aneurysmally dilated main pulmonary artery. The exact origin of the left pulmonary artery (LPA) was not clearly established prenatally. A postnatal echocardiogram of the neonate showed an abnormal origin of the LPA from the ascending aorta (hemitruncus). The neonate subsequently underwent surgical repair with a good outcome. We present a novel case of a TOF/APVS associated with an abnormal origin of the LPA from the ascending aorta.
Keywords: tetralogy of Fallot; absent pulmonary valve; left hemitruncus; fetal echocardiography